2020
DOI: 10.1016/j.jmoneco.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The optimal composition of public spending in a deep recession

Abstract: We study optimal monetary and fiscal policy under commitment in an economy where monetary policy is constrained by the zero lower bound on the nominal interest rate, and where the government can allocate spending to public consumption and public investment. We show that the optimal response to an adverse shock that precipitates the economy into a liquidity trap entails a small and short-lived increase in public consumption but a large and persistent increase in public investment, which lasts well after the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…When he estimates his model separately over zero lower bound periods and normal periods, he finds evidence of a slightly higher multiplier for government investment than government consumption during zero lower bound periods. Recall that Bouakez et al (2017Bouakez et al ( , 2019 showed that at the ZLB, the NK model predicted a flipping of the ranking of multipliers, with gov-ernment investment multipliers higher at the ZLB. Boehm's point estimates qualitatively support this prediction.…”
Section: Aggregate Evidencementioning
confidence: 99%
“…When he estimates his model separately over zero lower bound periods and normal periods, he finds evidence of a slightly higher multiplier for government investment than government consumption during zero lower bound periods. Recall that Bouakez et al (2017Bouakez et al ( , 2019 showed that at the ZLB, the NK model predicted a flipping of the ranking of multipliers, with gov-ernment investment multipliers higher at the ZLB. Boehm's point estimates qualitatively support this prediction.…”
Section: Aggregate Evidencementioning
confidence: 99%
“…The theoretical and empirical efforts and literature have dedicated a significant amount of work to evaluate these problems and issues, and Divino, Maciel, and Sosa (2020) for instance completely evaluated the exclusive influences of government spending and policies on the overall economic development and productivity of the country. In a pioneering effort, Bouakez, Guillard, and Roulleau-Pasdeloup (2016) also suggested a model evaluate the direct connection between the composition of public expenditure (PE) and economic development. This all indicates that much of the efforts have been completed in the past few years regarding government spending and its impacts on the overall economic situation of the country (Facchini & Seghezza, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal fiscal policy is analyzed by e.g. Eggertsson and Woodford (2006), Eggertsson (2006), Schmidt (2013), Nakata (2016, Bilbiie et al (2018) and Bouakez et al (2016), among others.…”
Section: Introductionmentioning
confidence: 99%